Diversity, Disparity and Diabetes: Voices of Urban First Nations and Métis People, Health Service Providers and Policy Makers - Ghosh, Hasu (Université d'Ottawa / University of Ottawa, 2013)
While previous health research with Aboriginal populations focused almost exclusively on Aboriginal Peoples of First Nations descent living on reserves or in isolated rural communities in Canada, this study focusing on diabetes aimed to engage Aboriginal Peoples of First Nations and Métis descent living in an urban Ontario setting. Type 2 diabetes mellitus is a progressive metabolic disorder that affects Aboriginal Peoples of Métis and First Nations descent disproportionately compared to the rest of the Canadian population. To understand this disparity in diabetes incidence and to address issues with existing diabetes prevention and management strategies, this study: a) explores the perceptions surrounding Type 2 diabetes and its prevention from First Nations and Métis community people and health service providers and policy makers; and b) informs the existing diabetes prevention, management and care strategies in light of these perceived understandings. Primary data was collected through 40 in-depth one-on-one narrative interviews with First Nations and Métis people, health service providers and policy makers. Thematic codes that emerged through the narrative analysis of this data revealed that to fully understand the social determinants of diabetes in an urban First Nations and Métis people’s context required the application of intersectionality theory, since production of First Nations and Métis diabetes is socially determined and deeply intersectional. By combining the concepts of the social determinants of health and intersectional approaches, narrative analysis of the primary data revealed that diversities in socio-economic, cultural, legal and spatial contexts determine First Nations and Métis people’s life choices and have a strong bearing on their health outcomes. First Nations and Métis participants’ narratives revealed that dimensions of marginalization were reflected not only through inadequate material resources, but also through intersections of multiple factors such as colonial legacies, stereotyping, legal statuses, and the pan-Aboriginal nature of government policies and services. First Nations and Métis community members indicated that preventive programming aimed at avoiding or managing diabetes should be grounded in balancing and restoring the positive aspects of physical, mental, spiritual and emotional health and should also balance their diverse needs, lived realities, and social circumstances. The views of health service providers and policy makers captured in this thesis tended to reflect an understanding of diabetes causation grounded in both biomedical and intersecting social determinants of health. At the pragmatic level, however, the solution to this health issue presented by health service providers and policy makers addresses only the measurable individualistic biomedical risk factors of diabetes. Policy makers also discussed the need for developing qualitative indicators of the success of presently implemented health programs. Overall, the results of this study indicated that effective diabetes prevention and management strategies for urban First Nations and Métis people must recognize and address the diversities in their historical, socio-economic, spatial and legal contexts as well as their related entitlement to health services. A comprehensive diabetes prevention strategy should target the social determinants of health that are specific to urban First Nations and Métis people and must build on community strengths.